Do the Palaearctic subgenera of Podistra Motschulsky, 1839 really occur in North America: description of P. ( Pidostria ), subgen. nov. (Coleoptera: Cantharidae) - Kazantsev, Sergey V. (Zootaxa, 2023)
A new subgenus, Pidostria subgen. nov., is described in Podistra Motschulsky, 1839 for a North American member of the genus, all the remaining subgenera thus become confined to the Palaearctic region. The new taxon is retained in Podistra due to the structure of its aedeagus, despite the differences in such morphological characters, as elytral vestiture, shape of ultimate palpomeres and protarsal claw dent. Pseudoabsidia Wittmer, 1969, syn. nov. is proposed as a new synonym of Podistra. Podistra (Absidia) pentheri Ganglbauer, 1922 is transferred to Pakabsidia Wittmer, 1972 as Pakabsidia pentheri (Ganglbauer, 1922), comb. nov. Podistra longicornis Wittmer, 1978 is transferred to Cantharis Linnaeus, 1758 as Cantharis longicornis (Wittmer, 1978), comb. nov. Podistra (Pseudoabsidia) sanbernardensis (Fender, 1972) and Cantharis (Cyrtomoptila) sierrae (McKey-Fender, 1950) are transferred to Podistra incertae sedis. Provided are a key to the subgenera, a list of species of Podistra and a map of their distribution worldwide.